STANDARDS FOR GOOD PHARMACY PRACTICE DEVELOPMENT - Gala, L. O. (Zaporozhye Medical Journal, 2014)
According to the order of the Ministry of Health of Ukraine of 30.05.2013 No 455 that joints guideline of the World Health Organization and the International Pharmaceutical Federation "Good pharmacy practice: standards for quality of pharmacy services" (GPP Guidelines) it was recommended to use Good Pharmacy Practice (GPP) standards as a baseline information source for the development. AIM OF RESEARCH. To suggest methodological approaches for the development of national GPP standards in Ukraine, to study the typical structure of GPP standards. RESEARCH MATERIALS AND METHODS. GPP guideline, pharmacy practice guidelines of a variety of countries of the world were selected as research objects. <a href="https://www.google.com.ua/url?sa=t&rct=j&q=&esrc=s&source=web&cd=4&cad=rja&ved=0CEYQFjAD&url=http%3A%2F%2Fscholar.lib.vt.edu%2Ftheses%2Favailable%2Fetd-07242002-111511%2Funrestricted%2FThesisDraft.pdf&ei=h2dWUvDwA4XTtAa_8YG4Dw&usg=AFQjCNGCSpK3ZC8MREZ4vcM7U0qowD-upQ">Comparative analytical method, analogy and generalization methods were used. RESULTS AND DISCUSSION. GPP guideline provides a framework within which each country has to offer its own national standards for the provision of qualitative pharmaceutical services for population. On our opinion, the GPP standard – is recommendatory document which may acquire a normative character in the future that defines the list of standards and requirements for the provision of qualitative pharmaceutical care and conformity of pharmacies to criteria which allow to assess their activities as appropriate. We developed a structure of national GPP standard, which must contain the following elements: 1) title of the standard; 2) introduction; 3) terms and definitions; 4) symbols and abbreviations used in the text of the standard; 5) scope of application; 6) requirements for activities; 7) appendixes; 8) bibliographic resources; 9) notes. CONCLUSIONS. Professional pharmaceutical associations have got a leadership role in the development of pharmacy practice standards in different countries. GPP standards are used for control of regulators and pharmacies owners and as a method of self-assessment of service quality for professionals.